50 años de La maffia (1972), de Leopoldo Torre Nilsson: representaciones de la mafia ítalo-rosarina. Interacciones entre narrativas periodísticas, literarias y cinematográficas - Setton, Román Pablo (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The following article analyzes the film La maffia (1972), by Leopoldo Torre Nilsson. I try to show how the film configures a representation of the Sicilian mafia of the 1930s less from the historical facts than from the speech of the journalistic chronicle of the time, of the Hollywood and Argentine cinematographic tradition and also from the literary tradition and the political imaginary linked to Peronism. In turn, the film itself – enormously successful with critics and audiences alike – goes on to feed the Argentine imaginary of that mafia, which continues to operate largely as an important influence on the political imaginary.